2018
DOI: 10.1111/anu.12673
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, muscle and liver composition, blood traits, digestibility and gut bacteria of beluga (Huso huso) juvenile fed different levels of soybean meal and lactic acid

Abstract: The objective of this study was to assess the effects of fishmeal (FM) replacement with 0, 350 or 700 g/kg soybean meal (SBM) in combination with the supplementation of lactic acid (LA; 0, 10 or 20 g/kg) in the diets of juvenile beluga sturgeon (Huso huso; 700 ± 30 g). Nine isonitrogenous (400 g/kg protein) and isoenergetic (18 MJ/kg) diets were fed to beluga ad libitum, three times a day, for 60 days. The results showed that replacing FM with SBM without LA significantly reduced fish growth; on the other hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 54 publications
5
36
0
Order By: Relevance
“…The amount of feeding and frequency was estimated based on the table presented by the manufacturing company of shrimp feed (Table ). The analysis of proximate composition of the diets (protein, lipid and ash contents) was done according to AOAC method (AOAC, ; Esmaeili, Kenari, et al, ; Matani Bour, Esmaeili, & Abedian Kenari, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of feeding and frequency was estimated based on the table presented by the manufacturing company of shrimp feed (Table ). The analysis of proximate composition of the diets (protein, lipid and ash contents) was done according to AOAC method (AOAC, ; Esmaeili, Kenari, et al, ; Matani Bour, Esmaeili, & Abedian Kenari, ).…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of proximate composition of the diets (protein, lipid and ash contents) was done according to AOAC method (AOAC, 2000;Matani Bour, Esmaeili, & Abedian Kenari, 2018).…”
Section: Pond Conditionsmentioning
confidence: 99%
“…Being carnivorous, Beluga sturgeon was come from the Huso genus and has the higher protein requirement to satisfy tissue growth and maintenance [17]. Meanwhile, there was evidence showed that replacing fishmeal with soybean meal without lactic acid significantly reduced growth performances of beluga, which further suggested that animal protein plays a key role in beluga diets due to their feeding habits [18]. The phylogenetic relationship between Siberian sturgeon and Beluga sturgeon is very close, because they belong with the same family.…”
Section: Introductionmentioning
confidence: 99%
“…Today, sturgeon farming has been expanded rapidly in the world. Among the aquaculture of sturgeons, great sturgeon, Huso huso , has made a promising candidate because of high growth, resistance to stress factors and reception of formulated diets (Matani Bour et al, 2018; Pajand et al, 2017).…”
Section: Introductionmentioning
confidence: 99%